Pengaruh pelatihan kerja dan pengembangan terhadap kepuasan kerja dimediasi self Efficiency di PT. Bahana Unindo Teknik - Rista Ndruru; Windy Romatua Malau; Retno Purwani Setyaningrum (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This research aims to investigate the influence of job training and career development on job satisfaction, utilizing a qualitative approach while considering the concept of self efficacy as a mediator.The aim of this journal is to investigate and analyze the impact of job training in career development on the level of employee job satisfaction at PT. Bahana Unindo Teknik, taking into account the mediating role of self-efficacy. The research method employed in this study is a survey conducted among employees in the injection manufacturing sector at PT. Bahana Unindo Teknik. Data was gathered through a questionnaire encompassing variables such as job training, career development, self-efficacy, and job satisfaction. The results of data analysis using relevant statistical approaches revealed a significant positive impact of job training and career development on job satisfaction. Additionally, self efficacy was identified as a mediator that moderates the relationship between job training, career development, and job satisfaction. Keyword : job training; career development; job satisfaction; self-efficacy